Early snowmelt and sea ice breakup enhance algal export in the Beaufort Sea - Nadaï, Gabrielle; Nöthig, Eva-Maria; Fortier, Louis; Lalande, Catherine (Progress in oceanography, 2021)
•Sediment traps were deployed at three sites in the Beaufort Sea.•The early onset of snowmelt led to an early release of ice algae in 2016.•The early melt led to the highest diatom and phytoplankton carbon fluxes in 2016.•Annual phytoplankton carbon fluxes ranged from 13 to 520 mg C m−2 yr−1 in 2016. Microalgal cells collected with moored sediment traps deployed during three to five annual cycles at three sites in the Beaufort Sea were identified to investigate variations in the timing, abundance and composition of microalgal fluxes in relation to snow and sea ice cover. The investigation period encompassed two extremes in snow and sea ice conditions: a delayed melt due to an ice rebound in 2013 and a premature snowmelt and sea ice breakup that led to an ice-free Beaufort Sea in 2016. Diatoms dominated the microalgal fluxes, with the pelagic centric diatoms Thalassiosira spp. and the ice-associated pennate diatoms Fragilariopsis spp. consistently collected at the three sites. The export of the ice-obligated algae Nitzschia frigida indicated the release of sea ice algae at the onset of snowmelt. Early snowmelt and sea ice breakup in 2016 contributed to an early start of ice algae release accompanied with early peaks in diatom fluxes and higher diatom and phytoplankton carbon (PPC) fluxes during spring and summer. Conversely, delayed sea ice algae release, low diatom fluxes, and low PPC fluxes were observed when snowmelt and sea ice breakup occurred late over the Mackenzie shelf break. The amount of diatoms exported at ~100–300 m also likely depended on a match or mismatch between algal production and zooplankton grazing. Variations in the snow and sea ice regimes at the regional scale therefore directly impact the timing and magnitude of microalgal export and its contribution to particulate organic carbon flux in the Arctic Ocean. With global warming, the ongoing sea ice reduction in the Arctic Ocean may increase PPC fluxes to the seafloor and potential carbon sequestration at depth.